Embodiment" in phenomenology of Husserl, Merleau-Ponty, Levinas - Mehdi khabbazi kenari; Safa Sebti (حکمت و فلسفه, 2016)
In Phenomenological approach , regardless of the rules and rationality, the body is seen as a phenomenon that puts the subject exposed to the experience and sensibility. In this approach, the debate over the relationship between the subject , the world and the body is not based on the ontology of the subject and not on the basis of his knowledge of the world , but based on his experience and somatic proximity with the world. This paper seeks to address the phenomenology of Husserl , Merleau-Ponty and Levinas , with a focus on the body and the concept of embodiment , analyzes the contact points as well as differences in approaches and ideas of this philosophers. In the current study, based on the views of the philosophers, we are trying to respond to intertwined questions which are all linked with the body and embodiment of the subject . Also, we want to know how embodiment subject understands the world. The result is that, the body is not the means or the way to understand the world, but embodiment is the situation for vital living in the world and the possibility for our moral living whit the other. This article by phenomenological approach based on the books and articles by means of descriptive - analytical and critical comparison of the philosophers , seeks for answers to the research questions.